2022
DOI: 10.3389/fneur.2022.889884
|View full text |Cite
|
Sign up to set email alerts
|

Topological relationships between perivascular spaces and progression of white matter hyperintensities: A pilot study in a sample of the Lothian Birth Cohort 1936

Abstract: Enlarged perivascular spaces (PVS) and white matter hyperintensities (WMH) are features of cerebral small vessel disease which can be seen in brain magnetic resonance imaging (MRI). Given the associations and proposed mechanistic link between PVS and WMH, they are hypothesized to also have topological proximity. However, this and the influence of their spatial proximity on WMH progression are unknown. We analyzed longitudinal MRI data from 29 out of 32 participants (mean age at baseline = 71.9 years) in a long… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…We observed that presumably healthy individuals with higher initial WMH volumes tend to exhibit greater PVS volumes, and that, over the subsequent years, WMH can form around PVS (see Fig. 1E ), emphasising their interdependence and potentially shared underlying cardiovascular or ageing-related mechanisms(18,54,66). Additionally, baseline WMH and PVS rates of change of CSO and BG, respectively, correlated with one another, suggesting that future studies should explore the hypothesis of recurrent time-lagged associations.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…We observed that presumably healthy individuals with higher initial WMH volumes tend to exhibit greater PVS volumes, and that, over the subsequent years, WMH can form around PVS (see Fig. 1E ), emphasising their interdependence and potentially shared underlying cardiovascular or ageing-related mechanisms(18,54,66). Additionally, baseline WMH and PVS rates of change of CSO and BG, respectively, correlated with one another, suggesting that future studies should explore the hypothesis of recurrent time-lagged associations.…”
Section: Discussionmentioning
confidence: 80%
“…Numerous cross-sectional studies support the positive association between PVS and WMH(2) and a few even provide evidence of WMH developing in the proximity of PVS(54). We used correlational analysis to determine whether baseline regional WMH volumes explained part of the variance in regional PVS rates of change in the presumably healthy subsample, after adjusting for age, sex, and years of education.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same cohort of community-dwelling individuals (LBC1936), the spatial proximity of WMHs with PVS was evaluated longitudinally ( n = 29, mean age = 71.9 years old), with images collected over three sessions at 3-year intervals ( Barnes et al, 2022 ). WMHs appeared to be adjacent to or co-localized with PVS, however, statistical analyses revealed no significant associations ( Barnes et al, 2022 ).…”
Section: Automated Segmentation Of Perivascular Spacesmentioning
confidence: 99%
“…Ramirez et al, 2015Berezuk et al, 2015Cai et al, 2015Zong et al, 2016Wang et al, 2016Niazi et al, 2018Piantino et al, 2020Ballerini et al, 2020aBallerini et al, 2020bValdés Hernández et al, 2020Zong et al, 2020Barisano et al, 2021bSepehrband et al, 2021 Ramirez et al, 2021Shen et al, 2021George et al, 2021Piantino et al, 2021Donahue et al, 2021 Langan et al, 2022Ranti et al, 2022Lynch et al, 2022, Preprint Barisano et al, 2022bHupfeld et al, 2022Barnes et al, 2022Kamagata et al, 2022Donahue et al, 2022Ramirez et al, 2022Jokinen et al, 2020Zong et al, 2020Wang et al, 2021Huang et al, 2021 Spijkerman et al, 2022 PVS measures can be broadly categorized as quantitative metrics (volume, count, and volume fractions), and morphological metrics (length, width, solidity, and tortuosity). Listed first are the methods that utlize classical image filtering technique.…”
mentioning
confidence: 99%